Sentiment Analysis on Cyanide Case After 'Ice Cold' Aired with NLP Method using Naïve Bayes Algorithm - Hizria, Rahmatika; Sarwadi, Sarwadi; Hasibuan, Rabiatul Adawiyah; Ritonga, Ramadhani; Rosnelly , Rika (Information Technology and Science (ITScience), 2024)
Information technology is developing increasingly rapidly, and the reach of the Internet has expanded even to remote areas. The public increasingly uses social media as a source of information that discusses all aspects of people's lives. Social media has a vital role for most people, one of which is the news of the cyanide coffee case. The Cyanide Coffee case was discussed again by netizens after Netflix raised this case in a documentary film entitled Ice Cold, which made the public even more convinced of the irregularities of the case. Based on this, sentiment analysis is needed to extract comments to obtain public opinion information. The sentiment analysis aims to create a sentiment model to determine public comments on this case. Therefore, this research was conducted to find out and classify public sentiment on the Cyanide Coffee Case using the Natural Language Processing (NLP) method, which is a text preprocessing process followed by the tokenization stage. Data filtering was used using Indonesian Stopwords, and then normalization was continued using Porter Stemmer. In this study, data collection was carried out based on public comments on Ice Cold shows on the TikTok platform using TikTok Comments Scraper. The test results show that the classification using naïve Bayes obtained the results of 22 negative comments, 4052 neutral comments and 34 positive comments. The classification results of this study are 87% accuracy, 97.6% precision, 87% recall, and 91.9% F-Score.